The Influence of Public Accountability and Transparency on the Effectiveness of Community Development Activity Budget Management: An Empirical Study in Sudirejo-I Urban Village, Medan City District, Indonesia - Renny Maisyarah; Agus Tripriyono; Muhammad Ricky gunawan (SEAN Institute, 2026)
This study aims to examine the effect of public accountability on the effectiveness of community activity budget management in Sudirejo-I Urban Village, Medan Kota District, Indonesia. Public accountability is a fundamental principle of good governance that promotes transparency, responsibility, and efficient utilization of public funds. This research employed a quantitative approach using an associative research design. Data were collected through questionnaires distributed to 109 respondents, including village officials, neighborhood heads, community leaders, and local residents. The collected data were analyzed using descriptive statistics, validity and reliability tests, simple linear regression, t-test, and coefficient of determination (R²) with SPSS Statistics. The findings reveal that public accountability was perceived to be at a good level (mean = 4.14), while the effectiveness of community activity budget management was categorized as effective (mean = 4.15). Regression analysis produced the equation Y = 12.318 + 0.731X, indicating a positive relationship between public accountability and budget management effectiveness. The hypothesis testing results showed a significant positive effect of public accountability on budget management effectiveness (t = 8.962, p < 0.001). Furthermore, the coefficient of determination (R² = 0.581) indicates that public accountability explains 58.1% of the variance in the effectiveness of community activity budget management. These findings suggest that strengthening transparency, compliance with regulations, information disclosure, and community participation can significantly improve financial governance and budget management effectiveness at the village government level.